Teaching later British literature : a thematic approach - Pionke, Albert D., 1974- (Anthem Press, 2019)
Designed for both first-time teachers of survey courses in later British literature and more experienced instructors seeking a new way to approach familiar material, 'A Handbook to Teaching Later British Literature' presents a synthetic and adaptable framework for guiding students through British literary history from the 1780s through the 1940s.
Keywords: British literature -- Study and teaching.; Littérature britannique -- Étude et enseignement.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; LANGUAGE ARTS & DISCIPLINES -- Study & Teaching.